IDENTIFYING PREDICTORS OF A DIFFICULT THYROIDECTOMY - Mok, Valerie M. (2014)
INTRODUCTION: A Thyroidectomy Difficulty Scale (TDS) was previously developed that identified more difficult operations, which correlated with longer operative times and higher complication rates. The purpose of this study was to identify pre-operative variables predictive of a more difficult thyroidectomy using the TDS. METHODS: A four item, 20-point TDS, was used to score the difficulty of thyroid operations. Patient and disease factors were recorded for each patient. Difficult thyroidectomy (DT) and non-difficult thyroidectomy (NDT) patients were compared. A final multivariate logistic regression model was constructed with significant (p<0.05) variables from a univariate analysis. RESULTS: 189 patients were scored using TDS. 69 (36.5%) suffered from hyperthyroidism, 42 (22.2%) from Hashimoto’s, 34 (18.0%) from thyroid cancer and 36 (19.0%) from multinodular goiter. Among hyperthyroid patients, the DT group had a greater number preoperatively treated with Lugol’s potassium iodide (81.6% DT vs. 58.1% NDT, p=0.032), presence of ophthalmopathy (31.6% DT vs. 9.7% NDT, p=0.028) and presence of (>4 IU/mL) anti-thyroglobulin antibodies (34.2% DT vs. 12.9% NDT, p=0.05). Using multivariate analysis, hyperthyroidism (OR 4.35, 95% CI 1.23–15.36, p=0.02), presence of anti-thyroglobulin antibody (OR 3.51, 95% CI 1.28–9.66, p=0.015), and high (>150 ng/mL) thyroglobulin (OR 2.61, 95% CI 1.06–6.42, p=0.037) were independently associated with DT. CONCLUSION: Using TDS, we demonstrated that a diagnosis of hyperthyroidism, pre-operative elevation of serum thyroglobulin and anti-thyroglobulin antibodies are associated with DT. This tool can assist surgeons in counseling patients regarding personalized operative risk and improve OR scheduling.